Penularan Virus Bergejala Mosaik Pada Tanaman Melon (Cucumis melo L.) Secara Mekanis dan Melalui Vektor Kutu Daun - KHULUQ, MISBAHUL; PHABIOLA, TRISNA AGUNG; WIJAYA, I NYOMAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2020)
Transmission of Symptomatic Mosaic Virus in Melon (Cucumis melo L.) Mechanically and Through the Aphids Vector Melon (Cucumis melo L.) is one of the horticulture plants that is widely cultivated and consumed by the people of Indonesia. But the decrease in yield due to an OPT attack (plant disrupting organisms) is a major concern. Among the pests that play a role in reducing the yield of melons are viruses and insect vectors. Aside from being a pest, aphid insect also act as vector transmitters of viruses that cause mosaics in melon plants. The method of transmission in this research used the method of transmission mechanically and through aphids vectors. The aim of this research was to examine the potential transmission of Potyvirus wich caused mosaic on melon mechanically and through the vector Aphis gossypii. The parameters are the type of symptoms, the percentage of the disease and the intensity of the disease attack. The variations of symptoms showen were dark green mosaic patterns, yellow mosaic patterns, vein-banding and malformations. The results of the transmission test were proven by molecular identification using the Reverse Transcription Polymerase Chain Reaction method. The results explained that the Potyvirus could be transmitted mechanically with disease incidence of 100%, disease intensity of 42% and through Aphis gossypii vector with a disease incidence of 90%, disease intensity of 28%. The test was proven using the RT-PCR method with CIFor and CIRev primers which showed amplicon product 700 pb.